Fast Encoding Algorithm for Vector Quantization- Based on Block Truncation Coding Technique - Hameed, Maha (Iraqi Journal of Science, 2025)
An adaptation be thed to improve the compressibility of the BC ay utilizing VO to repreheat the binary form of the codac image produced from the BTCsemadVO pased image coding requites o" codebeck search for cach, imput vector te find out the best-matched coceword, it is a time consuming process in our presence work, a fast algorithm for vector quantizing image data is pronosed the algorithm is proved powertul